Penerapan Metode Tebak Kata dalam Meningkatkan Pemahaman Siswa Belajar Peranan Politik Luar Negeri Indonesia Dalam Era Globalisasi - HIDAYATI, HIDAYATI (Komunitas Manajemen Kompetitif, 2017)
Abstract: teachers act as the manager of the learning process, develop teaching materials well, and improve the ability of students to listen to the lessons and master the educational goals they need to accomplish. Through the method of class actions implemented in SDN 023 Padau Jaya in grade social studies result observassi in cycle I-III illustrate the attitude of the students in following the lessons already provide a change in the behavior of pupils, especially in completing a given task, where students have been able to believed proved still late and has also been honest in completing tasks such as not cheating, but already showing civic attitude that is ready to give his devotion in implementing local togetherness. The application of the word tabak method can improve learning outcomes of civic education, especially in matter of understanding of the role of Indonesia's foreign policy in the era of globalization with the achievements of the KKM and attitudes pupil behavior. Keywords: method of charades, understanding learning